Description of the topographical changes associated to the different stages of the DsbA catalytic cycle - Vinci, Floriana (Cold Spring Harbor Laboratory Press, 2002)
This paper provides a description of the surface topography of DsbA, the bacterial disulfide-bond forming enzyme, in the different phases of its catalytic cycle. Three representative states, that is, oxidized and reduced protein and a covalent complex mimicking the DsbA-substrate disulfide intermediate, have been investigated by a combination of limited proteolysis experiments and mass spectrometry methodologies. Protease-accessible sites are largely distributed in the oxidized form with a small predominance inside the thioredoxin domain. Proteolysis occurs even in secondary structure elements, revealing a significant mobility of the protein. Many cleavage sites disappear in the reduced form and most of the remaining ones appear with strongly reduced kinetics. The protein within the complex shows an intermediate behavior. This variation of flexibility in DsbA is probably the determining factor for the course of its catalytic cycle. In particular, the great mobility of the oxidized protein might facilitate the accommodation of its various substrates, whereas the increasing rigidity from the complexed to the reduced form could help the release of oxidized products. The formation of the complex between PID peptide and DsbA does not significantly protect the enzyme against proteolysis, reinforcing the results previously obtained by calorimetry concerning the weakness of their interaction. The few cleavage sites observed, however, are in favor of the presence of the peptide in the binding site postulated from crystallographic studies. As for the peptide itself, the proteolytic pattern and the protection effect exerted by DsbA could be explained by a preferential orientation within the binding site.